FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ANTENATAL CARE(ANC) PADAIBU HAMIL DI WILAYAH KERJA PUSKESMAS CANDILAMAKOTA SEMARANG - Tasliah Tasliah; Laksmono Widagdo; Priyadi Nugraha P. (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Maternal Mortality Rate (MMR) in Semarang was increased from 122,25 per 100.000 live births in 2014 to 128,05 per 100.000 live births in 2015. The effort in order to accelerate the decline of MMR is to improve maternal health care by looking indicators K1 and K4 scope. The lowest K4 scope of visit of pregnant women in 2015 is Puskesmas Candilama (87,62%). This research aim to analyze the factors associated with the visit of antenatal care (ANC) in pregnant women in Puskesmas Candilama Semarang. This research was a quantitative research with cross sectional approach. The sample that used were total population with the result get 48 semples of third trimester pregnant women in Puskesmas Candilama. The data was collected by interview using a questionnaire. This research used data analyze of univariate and bivariate. Most respondents were not in the risk age category were age range of 20-35 years (87,5%), highly educated (87,5%) and unemployed (77,1%). Most respondents fully ANC visit (81,3%). The results of chi-square test showed that education (p=0,036), knowledge (p=0,001), attitude (p=0,001) and trust (p=0,010) were significantly associated with ANC visits. While the variables of age (p=0,328), occupation (p=0,350), availability of facilities (p=0,267), ease of access (p=0,574), support of health workers (p=0.909) and support of her husband (p=0.091) were not significantly associated with ANC visits. It is suggested to increase knowledge of pregnant women about interpretation, purpose, benefit and schedule of ANC visit, to provide information that trust about prohibition during pregnancy has nothing connect with the protection from negative spirit, and expected pregnant women to understand the ANC visit is not done if being sick.